PENGEMBANGAN MODEL KURIKULUM MADRASAH DINIYYAH TAKMILIYAH LP. MA'ARIF KAB. JEPARA DI ERA 4.0 - Ali As’ad; Alex yusron Al-mufti; M. Natsir (Edudeena : Journal of Islamic Religious Education, 2021)
Abstract: This research focuses on developing the content/materials of Madin Takmiliyah curriculum managed by LP. Ma’arif Jepara. This research aims to: a) Describe the strategic role of the LP. Ma’arif Jepara in Madin Education, b) developing the Madin Takmiliyah Curriculum model in Jepara regency c) measuring the effectiveness of Madin Takmiliyah curriculum development in Jepara regency. This study is a Research and Development research (R&D) using the ADDIE model, namely development with stages; analysis, design, development, implementation and evaluation. Data collection techniques using Dhelphi technique, FGD, product practicality testing, small-scale product trials and large-scale product trials. The results of the study explained that; a) LP Ma’arif Jepara’s education system includes supervision, coaching, and mentoring for each Madrasah Diniyah in various regions including management, learning and others. b) curriculum development includes content, methods and learning assessment., c) Madin curriculum model developed is considered effective with a barometer that is easy to translate, implement, evaluate and improve the management of the education system and human resources Abstrak: Penelitian ini fokus pada mengembangkan isi/materi kurikulum Madin Takmiliyah yang dikelola LP. Ma’arif Kab. Jepara. Penelitan ini bertujuan untuk: a) Mendeskripsikan peran strategis LP. Ma’arif, Kab. Jepara dalam Pendidikan Madin, b) mengembangkan model Kurikulum Madin Takmiliyah di Kab. Jepara, c) mengukur efektifitas pengembangan kurikulum Madin Takmiliyah di Kab. Jepara. Penelitian ini adalah penelitian pengembangan dan R & D dengan menggunakan model ADDIE, yaitu Pengembangan dengan tahapan; analisis, desain, development, implementation dan evaluation. Teknik pengumpulan data dengan menggunakan teknik Dhelphi, FGD, uji kepraktisan produk, uji coba produk skala kecil dan uji coba produk skala besar. Hasil penelitian memaparkan bahwa; a) LP Ma’arif Kab. Jepara dalam sistem pendidikan meliputi pengawasan, pembinaan, dan pendampingan bagi setiap Madrasah Diniyah di berbagai wilayah meliputi manajemen, pembelajaran dan lain-lain. b) pengembangan kurikulum meliputi isi, metode dan penilaian pembelajaran., c) model kurikulum Madin yang dikembangkan dinilai efektif dengan barometer mudah diterjemahkan, dilaksanakan, dievaluasi dan meningkatkan manajemen sistem pendidikan dan SDM.